Congenital hypothyroidism missed on screening. Issue 2 (February 1986) - Grant, G A; Carson, D J; Reid, M M; Hutchinson, J M
Abstract : Three patients with congenital hypothyroidism missed on routine screening due to normal low thyrotrophin concentrations in the neonatal period presented in later childhood. Clinicians should remain aware of hypothyroidism as a cause of morbidity in early childhood despite a national screening programme.